PERANCANGAN 3D PRINTING CARTESIAN BERBASIS FUSED DEPOSITION MODELLING DENGAN UKURAN 200 X 200 X 200 mm - Herman Budi Harja; Erfin Erfiansyah; Novi Saksono; Risky Ayu Febriansyah; Mohammad Fauzi (P3M Politeknik Negeri Indramayu, 2023)
The technology of adding manufacturing or 3D printing is one of the main issues in the concept of technology 4.0. The construction design of the 3D printing machine and the deflection of its construction significantly affect the accuracy of the dimension and shape the printed product. The study aims to obtain a construction design of a cartesian type 3 D printing machine based on fused deformation modelling, and to verify the maximum value of the deflection of the machine axis. The study method used VDI222, calculation analysis, and Finite Element Analysis (FEA) simulation using CAE Solidworks software to verify the strength and deflection of the machine design construction. The study results show the construction design of 3D printing machine has been obtained according to the requirement. The verified maximum deflection value is 0.036 mm, hence the maximum error in the dimensions and shape of the printed product for each layer will still be within the standard tolerance. In addition, its maximum deflection value is verified within the radial clearance value of each determined machine axis bearing.